2015
DOI: 10.1111/jbfa.12110
|View full text |Cite
|
Sign up to set email alerts
|

Star CEOs or Political Connections? Evidence from China's Publicly Traded Firms

Abstract: This paper studies China's “star CEOs” defined as members of the National People's Congress (NPC) or the National Committee of the Chinese People's Political Consultative Conference (CPPCC) and “politically connected” CEOs who have previous government or military experience. We evaluate the effect of “star CEOs” and “politically connected” CEOs on firm performance and CEO compensation. We find that announcement date returns, CEO compensation and incentives are all higher in firms that appoint “star CEOs”. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 63 publications
(148 reference statements)
1
44
0
Order By: Relevance
“…We also study the association between the earnings management behaviors and the presence of politically connected independent board members. Extant literature has established that political connections have a significant impact on firm performance all over the world (Li, Meng, Wang, & Zhou, 2008;Niessen & Ruenzi, 2010;Wu, Wu, Zhou, & Wu, 2012), and this effect is stronger in transition economies (Conyon, He, & Zhou, 2015;Li & Zhang, 2007). China as the largest developing economy entity has attracted a lot of attention in academia, and ISSN 2162-3082 2017 a number of studies have explored the earnings management behaviors of Chinese firms (C. J.…”
Section: Introductionmentioning
confidence: 99%
“…We also study the association between the earnings management behaviors and the presence of politically connected independent board members. Extant literature has established that political connections have a significant impact on firm performance all over the world (Li, Meng, Wang, & Zhou, 2008;Niessen & Ruenzi, 2010;Wu, Wu, Zhou, & Wu, 2012), and this effect is stronger in transition economies (Conyon, He, & Zhou, 2015;Li & Zhang, 2007). China as the largest developing economy entity has attracted a lot of attention in academia, and ISSN 2162-3082 2017 a number of studies have explored the earnings management behaviors of Chinese firms (C. J.…”
Section: Introductionmentioning
confidence: 99%
“…), compensation and performance premium (Conyon et al. ), mergers and acquisitions (Liu et al. ), positive abnormal returns (He et al.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In China, studies have found that political connections entitle politically connected firms to favourable terms such as in their IPO (Francis et al 2009), lending terms and firm performance , compensation and performance premium (Conyon et al 2015), mergers and acquisitions (Liu et al 2016), positive abnormal returns (He et al 2014) and higher cash dividends (Su et al 2014). Tao et al (2017) find politically connected ST firms receive more government subsidies.…”
Section: The Political Versus the Social View Of Government Interventionmentioning
confidence: 99%
“…For example, Civilize et al (2015) used hand-collected data from 1985 to 2008 and found that politically connected firms enjoyed higher realized returns than nonpolitically connected firms, especially in competitive and regulated industries. Examining "star-CEOs" in Chinese listed firms, Conyon et al (2015) found that these strong politically connected companies have much higher announcement returns and higher CEO compensation and these premiums are largely driven by the political connections of these "star-CEOs." In cross-border M&A research fields, Brockman et al (2013) used M&A samples from 22 countries and found that politically connected acquirers have more than 15% higher abnormal returns than unconnected firms, and these abnormal returns are much higher in weak legal systems or in highly corrupt countries.…”
Section: Literature Review Of Political Connectionsmentioning
confidence: 99%
“…On the other hand, there are potential costs to the firm's own political connections, such as higher volatility, high beta, poor corporate governance, and lower levels of equity-based compensation (Kostovetsky, 2015;Shen, Lin, & Wang, 2015). These somewhat opposing elements explain why some empirical studies find that political connections generate value for shareholders (Brockman, Rui, & Zou, 2013;Civilize, Wongchoti, & Young, 2015;Conyon, He, & Zhou, 2015), whereas others fail to find any positive effect in this regard (Faccio, 2010;Mitchell & Joseph, 2010;Peng & Luo, 2000).…”
Section: Introductionmentioning
confidence: 99%